What's Law Got To Do With It?: Historical Considerations on Class Struggle, Boundaries of Constraint, and Capitalist Authority - Palmer, Bryan D. (Osgoode Hall Law Journal, 2003)
This article offers a preliminary theoretical statement on the law as a set of boundaries constraining class struggle in the interests of capitalist authority. But those boundaries are not forever fixed, and are constantly evolving through the pressures exerted on them by active working-class resistance, some of which takes the form of overt civil disobedience. To illustrate this process, the author explores the ways in which specific moments of labour upheaval in 1886, 1919, 1937, and 1946 conditioned the eventual making of industrial legality. When this legality unravelled in the post-World War II period, workers were left vulnerable and their trade union leaders increasingly trapped in an ossified understanding of the rules of labour-capital-state relations, rules that had long been abandoned by other players on the unequal field of class relations. The article closes by arguing for the necessity of the workers' movement recovering its civil disobedience heritage.